2011
DOI: 10.1007/s10561-011-9243-7
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus (AAV) based gene therapy for eye diseases

Abstract: Gene therapy emerged as important approach in treatment for many inborn disorders caused by genetic defects, as well as other diseases. This manuscript focused on Adeno-associated virus (AAV) based gene therapy to eye diseases. The paper firstly introduced the AAV vectors and the techniques of eye delivery, then summarized some tested genes that were used in past treatment to retinal degeneration disorders. Finally the paper discussed the updated optogenetics and its roles in AAV based gene therapy for eye dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This is in accordance to what is described by Haase et al, 10 which has shown these plasmids to originate the strongest luciferase expression in vivo, as the hCMV promoter is less affected by epigenetic silencing events than CMV. 12 Although our in vivo study has shown a low number of transfected cells, upon comparison with other studies, where these systems were combined with chitosan nanoparticles for corneal gene delivery 25 or AAVs used for retinal transduction, 26 the amount of DNA we used was significantly lower than in other studies (100 ng compared with 1.5 mg 25 ). However, our results show that by using only 100 ng of DNA, we could achieve a transfection efficiency of 1.5-2% of the ganglion cells.…”
Section: Discussionmentioning
confidence: 58%
“…This is in accordance to what is described by Haase et al, 10 which has shown these plasmids to originate the strongest luciferase expression in vivo, as the hCMV promoter is less affected by epigenetic silencing events than CMV. 12 Although our in vivo study has shown a low number of transfected cells, upon comparison with other studies, where these systems were combined with chitosan nanoparticles for corneal gene delivery 25 or AAVs used for retinal transduction, 26 the amount of DNA we used was significantly lower than in other studies (100 ng compared with 1.5 mg 25 ). However, our results show that by using only 100 ng of DNA, we could achieve a transfection efficiency of 1.5-2% of the ganglion cells.…”
Section: Discussionmentioning
confidence: 58%
“…[17,18] The primary method of gene delivery in ocular space for treating various visual disorders employs viral-based gene transduction. [19][20][21][22] However, the viralbased gene delivery may not be ideal for clinical translation of optogenetics therapy for inherited retinal diseases dealing with geographic atrophies (GA), where patches of the retina have photoreceptor degeneration. Besides, the viral-based delivery method has several limitations, especially having no control over the spread of viral transduction in retina (eg, it transduces pan-retina when injected intravitreally).…”
Section: Introductionmentioning
confidence: 99%